Vitamin D status of pediatric epilepsy patients and evaluation of affecting factors - Serap Bilge; Sema Nur Taşkın (Italian Journal of Pediatrics)
Abstract Background The use of antiseizure medication in patients with epilepsy is one of the significant risk factors associated with abnormal vitamin D status. We aimed to identify risk factors related to hypovitaminosis D in pediatric patients treated with antiseizure medications. Method A cross-sectional retrospective cohort study was conducted on 127 pediatric epilepsy patients who received antiseizure drugs from December 2021 to December 2022. Demographic data, seizure types, diet, physical activity, duration, and types of antiseizure medications were analyzed. Results Among the 127 patients in this study, 53% were male, and the mean age was 9,1 ± 4,6 years (range: 2–17). The mean serum 25(OH)D level at baseline in winter/autumn was 24,2 ± 14,2 ng/mL; 47.0% of the patients were 25(OH) D deficient, 23% were 25(OH)D insufficient, and 30% had a vitamin D level within the normal range. The vitamin 25(OH) D level was 27,6 ± 12,2 in the epilepsy group with non-enzyme-induced antiseizure drugs, 21,76 ± 19,7 in the group with enzyme-induced antiseizure drugs, and 13,96 ± 7,9 in the group with combined antiseizure drugs (p < 0.001). Conclusion The number of antiseizure drugs, treatment with enzyme-induced antiseizure drugs, duration of epilepsy, abnormalities in magnetic resonance imaging, and etiology play important roles in determining the vitamin D level.